COMMUNITY RESPONSE RELATED TO ADDITION OF SERVICE HOURS IN PUBLIC HEALTH CENTER SEMARANG CITY - Ayu Dyah Pramesti; Septo Pawelas Arso; Nurhasmadiar Nandini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Public Health Center as a health facility provides access to health for individuals and groups. One of the innovations of the Semarang City Health Office in expanding community access to health services is the